Degradasi Zat Warna Metanil Yellow dengan Katalis TiO2 Menggunakan Metode Fotosonolisis - Reflia, Tiwi; Sanjaya, Hary; Budiman, Septian (Departemen Kimia FMIPA UNP, 2024)
The photosonolysis method has been investigated to degrade the metanil yellow in a sample solution using the catalyst of TiO2. This study aims to determine how the effect of adding catalyst mass to the degradation of metanil yellow. The variation of the mass of the catalyst used to degrade the metanil yellow dye is from 0.5 grams, 0.1 grams, 0.15 grams, and 0.25 grams at 120 minutes according to the optimum time. The UV-Vis spectrophotometer was used to calculate the absorbance of metanil yellow before and after degradation processes, while FTIR was used to determine the spectrum and functional groups before and after degradation. The results of the measurement of the maximum wavelength of the color of metanil yellow using a UV-Vis spectrophotometer were 434 nm with an absorbance value of 0.267. In the variation of the catalyst mass, the optimum mass obtained at 0.1 grams of TiO₂ catalyst with %D obtained was 35,58 %. In this study, the presence of hydroxyl radicals produced during photosynthesis plays an important role in degrading metanil yellow.